2020
DOI: 10.1002/hipo.23203
|View full text |Cite
|
Sign up to set email alerts
|

Medial temporal lobe regions mediate complex visual discriminations for both objects and scenes: A process‐based view

Abstract: Debate continues regarding the role of medial temporal lobe regions in object and scene processing. Considerable evidence indicates that the perirhinal cortex (PRC) plays an important role in the perception of objects—namely, in disambiguating complex objects that share conjunctions of features. These findings support a content‐specific view of medial temporal lobe functioning in which PRC is critically important for processing complex objects, while the parahippocampal cortex (PHC) and hippocampus (HC) may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 89 publications
1
10
0
Order By: Relevance
“…Recent evidence supports the key role of medial temporal lobe (MTL) and adjacent structures – the hippocampus, entorhinal cortex, perirhinal cortex and parahippocampal cortex, not just for memory, but also for visual perceptual processing (Moscovitch et al, 2016). Neuropsychological studies in patients with MTL damage, and functional MRI studies in healthy individuals provide strong evidence for the involvement of hippocampus and perirhinal cortex in visual discrimination tasks, especially when there are similarities and shared features between the simultaneously presented stimuli (Bonnen et al, 2021; Lawrence et al, 2020; Lech and Suchan, 2014). Because the GNA PC test entails comparing pairs of geometric shapes that are presented simultaneously, it does not require visual memory.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence supports the key role of medial temporal lobe (MTL) and adjacent structures – the hippocampus, entorhinal cortex, perirhinal cortex and parahippocampal cortex, not just for memory, but also for visual perceptual processing (Moscovitch et al, 2016). Neuropsychological studies in patients with MTL damage, and functional MRI studies in healthy individuals provide strong evidence for the involvement of hippocampus and perirhinal cortex in visual discrimination tasks, especially when there are similarities and shared features between the simultaneously presented stimuli (Bonnen et al, 2021; Lawrence et al, 2020; Lech and Suchan, 2014). Because the GNA PC test entails comparing pairs of geometric shapes that are presented simultaneously, it does not require visual memory.…”
Section: Discussionmentioning
confidence: 99%
“…Although resting-state data cannot be used to make direct claims about function, the observation that the MTL participates in four different resting-state networks could shed light onto a more complex function of this central structure in memory and other related processes. Although the traditional view on MTL function highlights its role in memory (Squire & Zola-Morgan, 1991), there is much evidence that the MTL is also involved in perceptual and attentional processes that may contribute to performance in different memory-demanding tasks (e.g., Lawrence et al, 2020;Bussey & Saksida, 2005;Baxter, 2009). Specifically, the perirhinal cortex has been previously considered as a part of the ventral visual stream (Bussey & Saksida, 2005) and involved in the perception of objects (for a review Baxter, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that PRC does not only receive information from the ventral visual stream, but additionally receives a number of inputs from spatial processing regions such as the PHC (Suzuki and Amaral, 1994a;Burwell and Amaral, 1998b). Accordingly, studies have reported evidence for similar processing of object-related and spatial information in the PRC under some circumstances (Berron et al, 2018;Lawrence et al, 2020).…”
Section: Discussionmentioning
confidence: 99%